Common and Specific Characteristics of Adolescent Bipolar Disorder Types I and II: A Combined Cortical Thickness and Structural Covariance Analysis - Kuang, Liangfeng; Gao, Weijia; Long, Zhiliang; Cao, Weifang; Cui, Dong; Guo, Yongxin; Jiao, Qing; Qiu, Jianfeng; Su, Linyan; Lu, Guangming (Frontiers in Psychiatry, 2022)
Background: By calculating cortical thickness (CT) and cortical structural covariance (SC), we aimed to investigate cortical morphology and cortical inter-regional correlations alterations in adolescent bipolar disorder type I (BD-I) and type II (BD-II) patients. Methods: T1-weighted images from 36 BD-I and 22 BD-II patients and 19 health subject controls (HCs) were processed to estimate CT. CT values of whole-brain were compared among three groups. Cortical regions showing CT differences in groups were regarded as seeds for analyzing cortical SC differences between-group. Relationship between CT and clinical indices was further assessed. Results: Both BD groups showed cortical thinning in several frontal and temporal areas versus HCs, and CT showed no significant difference between two BD subtypes. Compared to HCs, both BD groups exhibited reduced SC connections between left superior frontal gyrus (SFG) and right postcentral gyrus (PCG), left superior temporal gyrus (STG) and right pars opercularis and left STG and right PCG. Compared to HCs, decreased SC connections between left STG and right inferior parietal gyrus (IPG) and right pars opercularis and right STG were only observed in BD-I group, and left PCG and left SFG only in BD-II group. CT of right middle temporal gyrus was negatively correlated with number of episodes in BD-II patients. Conclusions: Adolescent BD-I and BD-II showed commonly decreased CT, while presented commonly and distinctly declined SC connections. This study provides a better understanding of cortical morphology and cortical inter-regional correlations alterations in BD, and crucial insights into neuroanatomical mechanisms and pathophysiology of different BD subtypes.